Ablation resistance and mechanism of ZrC-SiC-Yb2O3 ternary composite coatings fabricated by vacuum plasma spray. Issue 13 (October 2019) - Pan, Xiaohui; Niu, Yaran; Liu, Tao; Zhong, Xin; Li, Chong; Shi, Minhao; Zheng, Xuebin; Ding, Chuanxian
Abstract: In this work, ZrC-SiC-Yb2 O3 ternary composite coatings with different contents of Yb2 O3 (0, 5, 15 and 30 wt.%) were fabricated by vacuum plasma spray and the anti-ablation property above 2000 °C was evaluated. The results showed that the microstructures of the oxide scales were changed with different Yb2 O3 contents and then greatly modified the ablation resistant property of the composite coatings. The composite coating with 15 wt.% Yb2 O3 exhibited the best ablation resistance. The disappearance of SiC-depleted layer and formation of ZrCx Oy were observed. The mechanism of Yb2 O3 on the oxidation products and ablation behaviors of ZrC-SiC system was analyzed.